2020
DOI: 10.1080/02670836.2020.1839193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystal orientation on the size effects of nano-scale fcc metals

Abstract: The present work investigates the dominant mechanisms in the plasticity of nano-sized fcc metallic samples. Molecular dynamics simulations of nanopillar compression show that plasticity always starts with the nucleation of dislocations at the free surface, and the crystal orientation affects the subsequent microstructural evolution. The Schmid factor of leading and trailing partials plays a decisive role in leading to the twinning, or slip deformation. A significant difference is observed in the strength of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…In the case of simple shear loading, the obtained thresholds show dependence on the orientation of the sample in the loading device, which is in qualitative agreement with experimental results, e.g. [35,36]. Our study also reveals a strong link between the structure of the apparent yield surface and the lattice symmetry.…”
Section: Ideal Shear Strengthsupporting
confidence: 90%
See 1 more Smart Citation
“…In the case of simple shear loading, the obtained thresholds show dependence on the orientation of the sample in the loading device, which is in qualitative agreement with experimental results, e.g. [35,36]. Our study also reveals a strong link between the structure of the apparent yield surface and the lattice symmetry.…”
Section: Ideal Shear Strengthsupporting
confidence: 90%
“…Almost all dislocations mediating the explosive stress drop manage to escape to the boundaries, sometimes even producing pristine-topristine transition [16,34]. It was also observed that as the deformation volume of a material decreases, the effect of crystal orientation on the operative deformation mechanisms increases; in particular, the mechanical response of sub-micron defect-free nanopillars is different depending on whether they are deformed along high symmetry orientations or low symmetry orientations [35,36]. The compression tests on confined micropillars revealed higher (and therefore closer to theoretical limit) stresses of massive dislocation nucleation than in the presence of free surfaces [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…First, particles were selected for testing to achieve a range of particle diameters, but they clearly differed in other attributes, including crystallographic orientation and particle shape. Crystal orientation modifies the resolved shear stress for defects on particular crystal planes and also modifies the degree of spatial inhomogeneity of stress . Particle shape modifies various factors, including stress concentrations at corners, and the out-of-plane shape of FCC structures can influence which types of defects are favored .…”
Section: Resultsmentioning
confidence: 99%